Review paperAdverse events in allergy sufferers wearing contact lenses - Urgacz, Agnieszka; Mrukwa, Ewa; Gawlik, Radoslaw (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2015)
Allergy is the fifth leading chronic condition in industrialized countries among all ages, and the third most common chronic disease among children under 18 years old. Many of allergic patients also have problems with vision and want to improve their quality of life by wearing contact lenses. They are most frequently young and active individuals, for whom contact lenses provide greater convenience and more satisfying vision correction than spectacles. However, application of high quality and immunologically neutral products do not protect from allergic side reactions. Nowadays, eye-related allergy and contact lens wear concern larger and larger populations worldwide. The purpose of this review is to summarize the studies on ocular complications associated with wearing contact lenses. The article presents indications for allergic patients especially on the care system and wear schedule.